Piperidine-3, 4-diol and piperidine-3-ol derivatives of pyrrolo[2, 1-f][1, 2, 4]triazine as inhibitors of anaplastic lymphoma kinase. Issue 5 (1st March 2015) - Mesaros, Eugen F.; Angeles, Thelma S.; Albom, Mark S.; Wagner, Jason C.; Aimone, Lisa D.; Wan, Weihua; Lu, Lihui; Huang, Zeqi; Olsen, Mark; Kordwitz, Emily; Haltiwanger, R. Curtis; Landis, Amy J.; et al.
Graphical abstract: Abstract: The diastereoselective synthesis and biological activity of piperidine-3, 4-diol and piperidine-3-ol-derived pyrrolotriazine inhibitors of anaplastic lymphoma kinase (ALK) are described. Although piperidine-3, 4-diol and piperidine-3-ol derivatives showed comparable in vitro ALK activity, the latter subset of inhibitors demonstrated improved physiochemical and pharmacokinetic properties. Furthermore, the stereochemistry of the C3 and C4 centers had a marked impact on the in vivo inhibition of ALK autophosphorylation. Thus, trans -4-aryl-piperidine-3-ols (22 ) were more potent than the cis diastereomers (20 ).